Properties of particleboard 450kg/m3 from Sesenduk (Endospermum Malaccensis) / Norjihan A. Bakar - A. Bakar, Norjihan (2005)
Particleboard is one of many wood composites. Today, this panel is the most popular in furniture industry since this tremendous material replace plywood for building construction and furniture industry. In this study the Endospermum malaccessis selected as raw material with density 450kg/m3 also three percentage of resin Urea Formaldehyde that is 8%, 10% and 12% are used to make this particleboard. The physical and mechanical properties of this board will determine by several types of test. The result shows that the percentage of resin are used affecting the strength of this board. From this study the physical properties and some bending strength not reach the value of standard that has been specified.